Handbook of artificial intelligence techniques in photovoltaic systems : modeling, control, optimization, forecasting and fault diagnosis - Mellit, Adel; Kalogirou, Soteris (London ; San Diego, CA : Academic Press, 2022)
'Handbook of artificial intelligence techniques in photovoltaic systems provides readers with a comprehensive and detailed overview of the role of artificial intelligence (AI) in PV systems. Covering up-to-date research and methods of how, when, and why to use and apply AI techniques in solving most photovoltaic problems, this book will serve as a complete reference in applying intelligent techniques and algorithms to increase the efficiency of PV systems. Each chapter solves specific problem and can stand independently; this detailed book contains problem-solving data for challenges, including optimization , advanced control, output power forecasting, fault detection identification and localization, and real-time implementation of designed intelligent models (into FPGAs, DSPs, or MCs) and smart monitoring systems.'--Back cover.
Includes bibliographical references and index.
Keywords: Photovoltaic power systems -- Data processing; Artificial intelligence